HEALTH EDUCATION AS A MEANS OF PROMOTING A SUSTAINABLE SCHOOL ENVIRONMENT IN MOROCCO: TOWARDS A CONSCIOUS AND RESPONSIBLE SCHOOL COMMUNITY - Toufik Faik; Abdelaziz Saadani; Abdelaziz El Hammouchi; Ayoub Rouani (SocioEdu: Sociological Education, 2025)
The study investigates the role of health education within educational institutions, focusing on its impact on students' physical and psychological well-being, as well as its influence on the school environment. The research aims to assess how health education contributes to enhancing academic performance, fostering responsible environmental citizenship, and increasing health and environmental awareness among students. To achieve this, a field study was conducted employing an interactive methodology, including participant observation, data collection through questionnaires, and data analysis via content analysis techniques. Findings indicate that students possess limited health knowledge, which adversely affects their psychological and physical health and the overall school environment. Insufficient health awareness correlates with poor environmental practices, such as inadequate hygiene and widespread non-environmental behaviours. The study recommends that the Ministry of Education prioritise health education in strategic planning to cultivate a safe and conducive learning environment.